2019
DOI: 10.1039/c8ra08929a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platinum electrode materials and electrolysis processes on the preparation of acidic electrolyzed oxidizing water and slightly acidic electrolyzed water

Abstract: The effects of platinum electrode materials and electrolysis processes on the preparation of AEOW and SAEW have been systematically studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Pigment can be studied in depth by extraction technology and spectrometry for further analysis. The combination of high oxidation potential and available chlorine of SAEW is the main reason for the changes in the physicochemical properties of flour [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pigment can be studied in depth by extraction technology and spectrometry for further analysis. The combination of high oxidation potential and available chlorine of SAEW is the main reason for the changes in the physicochemical properties of flour [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…S. Wei et al reported similar results for EO water with low pH (2.2–2.7) and high ORP (>1100 mV) produced by electrolysis of a dilute NaCl solution in an electrolysis chamber with a Pt/Ti electrode [ 30 ]. The electrode material is the key parameter related to current efficiency and stability for the formation of active chlorine in EO water production [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further development research is still required for improvement in the existing design to increase the catalytic activity of the cathode and the anode, consequently increasing the overall performance of the system and reducing the system unit cost [11][12][13][14][15]. Despite their high resistivity toward oxidation, expensive noble's materials such as platinum give limitations in the water-splitting technology due to their high price and environmental issues such as corrosion [16][17][18]. To reduce the overall cost, diaphragm issues, and its complex assembly, an alternative of growing interest is diaphragm-free AEC.…”
Section: -Introductionmentioning
confidence: 99%